Microsoft forefront security administration guide - Varsalone, Jesse (Syngress Pub., 2008)
Microsoft Forefront is a comprehensive suite of security products that will provide companies with multiple layers of defense against threats. Computer and Network Security is a paramount issue for companies in the global marketplace. Businesses can no longer afford for their systems to go down because of viruses, malware, bugs, trojans, or other attacks. Running a Microsoft Forefront Suite within your environment brings many different benefits. Forefront allows you to achieve comprehensive, integrated, and simplified infrastructure security. This comprehensive suite of tools provides end-to-end security stretching from Web servers back to the desktop. This book will provide system administrators familiar with Syngress' existing Microsoft networking and security titles with a complete reference to Microsoft's flagship security products. * First book to address securing an entire Microsoft network from Web servers all the way back to the desktop. * Companion Web site provides best practices checklists for securing Microsoft operating systems, applications, servers, and databases. * Companion Web site provides special chapter on designing and implementing a disaster recover plan for a Microsoft network.